Comparative study on thiol drugs' effect on tert-butyl hydroperoxide induced luminol chemiluminescence in human erythrocyte lysate and hemoglobin oxidation. Issue 1 (February 2015) - Sajewicz, Waldemar; Zalewska, Marta; Milnerowicz, Halina
Highlights Three types of chemiluminescence kinetic under influence of thiol drugs. Various proportion of methemoglobin/hemichromes formation under influence of thiols. Thiol-derived secondary free radicals can be accelerated by the modification of globin. Heterogeneity of reaction mechanisms depends on structural relationship of thiol drugs. Thiol drugs can create danger of propagation and amplification of oxidative stress.